Enhancing Assessment Practices with Moodle: A Comprehensive Study on Teachers’ Use of Different Question Types and the Impact of FastTest PlugIn - Milagros Huerta-Gomez-Merodio; Maria-Victoria Requena-Garcia-Cruz (Applied Sciences)
This study investigates the evolution of online assessment practices through Moodle, a leading Learning Management System (LMS). It explores Moodle’s array of question types alongside the transformative impact of FastTest PlugIn (FTP) on educators’ assessment methods during and after the COVID-19 pandemic. This research examines the efficacy of various question types and import formats for large-scale question elaboration. Surveys have been conducted before and after developing courses to train educators on FTP. By analysing trends before and after adopting FTP, the study aims to gain insight into how educators from different universities and disciplines have adapted their assessment strategies among technological advancements. The introduction of FTP has significantly simplified question creation and integration within Moodle. The study also highlights differences in assessment practices between STEM and non-STEM disciplines. Surveys indicate that, following the FTP training course, the use of all question types has increased: Matching (35%), Missing Word (39%), and Cloze (22%). This work provides a comprehensive overview of current LMS trends and Moodle’s evolving role in educational technology. It emphasises the impact of technological advancements, such as FTP, on assessment practices and aims to offer actionable insights for enhancing online assessments.